XIAP overexpression promotes bladder cancer invasion in vitro and lung metastasis in vivo via enhancing nucleolin‐mediated Rho‐GDIβ mRNA stability. Issue 10 (28th December 2017) - Yu, Yonghui; Jin, Honglei; Xu, Jiheng; Gu, Jiayan; Li, Xin; Xie, Qipeng; Huang, Haishan; Li, Jingxia; Tian, Zhongxian; Jiang, Guosong; Chen, Caiyi; He, Feng; et al.
Abstract : Our recent studies demonstrate that X‐linked inhibitor of apoptosis protein (XIAP) is essential for regulating colorectal cancer invasion. Here, we discovered that RhoGDIβ was a key XIAP downstream effector mediating bladder cancer (BC) invasion in vitro and in vivo . We found that both XIAP and RhoGDIβ expressions were consistently elevated in BCs of N ‐butyl‐ N ‐(4‐hydroxybutyl)‐nitrosamine (BBN)‐treated mice in comparison to bladder tissues from vehicle‐treated mice and human BCs in comparison to the paired adjacent normal bladder tissues. Knockdown of XIAP attenuated RhoGDIβ expression and reduced cancer cell invasion, whereas RhoGDIβ expression was attenuated in BBN‐treated urothelium of RING‐deletion knockin mice. Mechanistically, XIAP stabilized RhoGDIβ mRNA by its positively regulating nucleolin mRNA stability via Erks‐dependent manner. Moreover, ectopic expression of GFP‐RhoGDIβ in T24T(shXIAP) cells restored its lung metastasis in nude mice. Our results demonstrate that XIAP‐regulated Erks/nucleolin/RhoGDIβ axis promoted BC invasion and lung metastasis. Abstract : What's new? Depth of tumor invasion in the bladder wall is closely associated with metastasis in bladder cancer. The factors driving invasion and metastasis in the bladder, however, are not fully known. Here, both X‐linked inhibitor of apoptosis protein (XIAP) and RhoGDIβ, a modulator of small GTPase activity, were found to be overexpressed in high‐grade invasive human bladder cancer specimens. Moreover, in cells, XIAP positively regulated RhoGDIβ expression and invasion, while in mice with bladder cancer, RhoGDIβ expression served a critical role in lung metastasis. Further study of these novel players could help improve preventative and therapeutic strategies for bladder cancer.